2017
DOI: 10.22319/rmcp.v8i4.4237
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of genomic values predicted using deregressed predicted breeding values as response variables

Abstract: Highly accurate predicted genetic values must be obtained at an early age to promote rapid genetic progress. The objectives of this study were to compare accuracies (R 2 ) of genomic values (GVs) and to estimate genetic correlation between true genetic values and genomic values obtained using predicted breeding values (EBV) and deregressed EBV (DEBV) as response variables. A first population, effective population size 800 and 100 generations, was simulated using the QMSim program to generate linkage disequilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…In dairy breeds, EBVs or deregressed EBVs are preferred as the dependent variable of GWAS. Research has shown that the deregressed EBVs could reliable in genomic analysis, but some studies showed that the accuracy of genomic analysis when using EBVs was only slightly lower than using deregressed EBVs [35,36]. In addition, a simulation study indicated that GWAS using EBVs or deregressed EBVs as the dependent variable with polygenic effect modeled had similar performance in controlling the false positive rates (FPR), even when using deregressed EBVs lowered the power in some degree [37].…”
Section: Gwas For Milk Traitsmentioning
confidence: 99%
“…In dairy breeds, EBVs or deregressed EBVs are preferred as the dependent variable of GWAS. Research has shown that the deregressed EBVs could reliable in genomic analysis, but some studies showed that the accuracy of genomic analysis when using EBVs was only slightly lower than using deregressed EBVs [35,36]. In addition, a simulation study indicated that GWAS using EBVs or deregressed EBVs as the dependent variable with polygenic effect modeled had similar performance in controlling the false positive rates (FPR), even when using deregressed EBVs lowered the power in some degree [37].…”
Section: Gwas For Milk Traitsmentioning
confidence: 99%
“…, permitindo avaliar o grau de similaridade entre as previsões (Momen et al, 2018;Ramírez-Flores et al, 2017). Foram utilizados as médias e os errospadrões das dez repetições do processo de simulação.…”
Section: • Valores Genéticos Estimadosunclassified